Development of Explanatory Text Assessment Instruments in Bahasa Indonesia Learning in Eight Grade of Smp 2 Linggo Sari Baganti, Kabupaten Pesisir Selatan - Irmaya candra; Atmazaki Atmazaki; Syahrul Syahrul (International Journal of Educational Dynamics, 2019)
This research aims to develop products of Bahasa Indonesia assessment instruments and learning process of the class in Eight Grade of SMP 2 Linggo Sari Baganti Kabupaten Pesisir Selatan, The products are consists of learning assessment and questionnaire assessments. This study adapted the development model. Based on the test results, the product has a validity (content and construct), reliability, practicality, applicability, as well as the attractiveness; and after revisions, the products assured as feasible to implement.